Problematika Pengembangan Profesi Pustakawan - Bukhori Bukhori (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
A library is a workplace where resources are organized, managed, stored, and gathered. Those resources are organized systematically so that users can access and use them as sources of information as well as of fun and enjoyable learning resources. Functional librarian officer is a public servant librarian who is given duties, responsibilities and full authorities and rights by the appointed officer to do librarianship tasks at the units of library, documentation, and information in a governmental organisation or other types of institution based on their certain skills which are practised independently. Considering the importance of librarians’ professional development, the author aims to examine this topic further.